(untitled) (Comparative Professional Pedagogy, 2022)
The article considers certain issues of increasing the effectiveness of teaching foreign languages to students of humanitarian institutions of higher education in Eastern Europe. It was shown that after the approval of the Common European Framework of Reference for Languages: Learning, Teaching, Assessment (CEFR) some radical changes took place in the methods of teaching foreign languages in many Eastern European countries. Taking into account the fact that among the most effective ways to improve the quality of foreign language education the CEFR determines an increase in the level of personal motivation of students to learn foreign languages, Eastern European educators more actively apply didactic solutions that meet as many criteria as possible, leading to deep learning of knowledge. Since motivation is an individual internal matter of the student, it is more logical for the teacher to create an educational context that the students themselves would recognize as motivating, rather than to directly motivate each student individually. The authors note that the creation of a motivational context, in particular for students of liberal arts colleges, takes place through a constant demand to combine the acquired knowledge (internalization) with what students have previously learned, reflected on and are able to express independently (externalization); emphasis on higher-order thinking (analysis, synthesis, evaluation) and performance of tasks that are more focused on mental activity (minds-on) than on physical activity (hands-on), while remembering that activating exercises are often mistakenly identified with physical activity load on students; students’ analysis of their own experience, attitudes, and values. The authors consider in detail three didactic solutions that are widely used by Eastern European teachers in the process of creating a motivational context for foreign language training of future humanitarians: the creation of conceptual maps, the «flipped classroom» method, and the method of duo-ethnographic dialogues. The authors conclude that the given didactic solutions relate to the field of issues, the study of which is determined by the students themselves as having personal value and being useful for their future career. By performing these exercises, students express their own points of view, present their personal understanding of the essence of the phenomena mentioned in the framework of the lesson, sometimes even revise and change their previous beliefs. Therefore, students’ progress in learning a foreign language is not only a consequence of studying, but is due to the motivating educational environment created by their teachers.